Associations with the use of multidimensional performance measures and the effectiveness of performance measurement systems / Rahat Munir, Kevin Baird and Zehao Si - Munir, Rahat; Kevin, Baird; Si, Zehao (Accounting Research Institute (ARI), 2012)
This paper examines the associations between: (i) business strategy and organisational culture with the usage of multidimensional performance measures and (ii) the use of multidimensional performance measures and information system characteristics with the effectiveness of performance measurement systems (PMSs). Using a mail survey method, data were collected from a random sample of 540 senior financial officers in Australian manufacturing organisations. The results revealed that business strategy (product differentiation and low cost) and a teamwork oriented culture were associated with the use of multidimensional performance measures. In addition, the use of multidimensional performance measures and all four information system characteristics (i.e. scope, timeliness, integration and aggregation) were associated with the performance related outcome dimension of PMS effectiveness, while the use of multidimensional performance measures and integrated information were associated with staff and strategic related outcomes. The study contributes to the literature by examining the use and effectiveness of PMSs.